Jaminan Kebebasan Beragama Menurut Undang-Undang Dasar Negara RI Tahun 1945 di Desa Mantadulu Kecamatan Angkona Kabupaten Luwu Timur - K, Hamzah; Rohana, Rohana (Program Studi Hukum Tata Negara (Siyasah) IAIN Palopo, 2020)
AbstractThe government in the village of Mantadulu, East Luwu Regency provides guarantees of freedom of religion according to the 1945 Constitution, based on articles 28E, 28I, and 29. Limitation on freedom can only be done through the law as stipulated in Article 28J of the 1945 Constitution, protection of religious freedom was guaranteed and protected by provisions constitutionality in Indonesia, law and human rights. Religious freedom has become a shared commitment even though there are two groups of thought, namely religious groups and nationalist groups (nationalities) giving the opinion that freedom of religion and freedom to practice worship according to their religion and guarantee of religious freedom from the perspective of Islamic law are in line with Islamic law. Not only provides recognition and guarantees, the magazine also obliges Muslims to give religious rights to non-Muslims according to their teachings. It was increasingly clear that Islam has guaranteed and protected freedom of religion and belief.Â AbstrakPemerintah di desa Mantadulu Kabupaten Luwu Timur memberikan Jaminan kebebasan beragama menurut UUD Tahun 1945, berdasarkan pasal 28E, 28I, dan 29. Pembatasan terhadap kebebasan hanya dapat dilakukan melalui UU sebagaimana diatur dalam Pasal 28J UUD 1945, perlindungan terhadap kebebasan beragama dijamin dan dilindungi oleh ketentuan konstitusional di Indonesia, hukum, dan HAM. Kebebasan beragama telah menjadi komitmen bersama meskipun terdapat dua kelompok pemikiran, yakni kelompok agamis, dan kelompok nasionalis (kebangsaan) memberikan pendapat bahwa kebebasan beragama serta kebebasan menjalankan ibadah menurut agamanya dan jaminan Kebebasan agama perspektif hukum Islam sejalan dengan hukum Islam. Tak hanya memberikan pengakuan dan jaminan, al-Qurâ€™an juga mewajibkan umat Islam untuk memberikan hak beragama bagi umat non-Muslim sesuai ajaran mereka. Semakin jelaslah bahwa Islam telah menjamin dan melindungi kebebasan beragama dan berkeyakinan.